Presenting Futures - Fisher, Erik.; Selin, Cynthia; Wetmore, Jameson M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
The ideas and imagery about the future that characterize nanotechnology today are shaped by multiple values and agendas which influence public investments,business strategies, infrastructure design, and public debate. Presenting Futures highlights a variety of ways that nanotechnology actors think about and seek to shape the future. It brings together social scientists, humanists, government officials, activist groups, designers, and public relations professionals into a multifaceted and at times conflicting dialogue through press releases, government reports, and advertisements taken from the front lines of the political discourse over nanotechnology, as well as original writings that situate nanotechnological futures within broader contexts. The chapters in this volume document various approaches to the future and how contemporary cultural conceptions about science, technology, and society are created and ultimately influence our own cognitive frames, social contests, and material practices. More than a catalogue of visions, the Yearbook is designed to give social scientists, natural scientists, and the general public an opportunity to explore, reflect on, and ultimately critique these futures. In asking not so much what the future of nanotechnology may be, but rather how different social groups and organizations imagine and anticipate it, the Yearbook offers a series of starting points for exploring the role of the future in the present.
Nanotechnology: The Future Is Coming Sooner than You Think -- The Workers$1 (BPush to Democratize Nanotechnology -- Thinking Longer Term about Technology -- Constructive Technology Assessment and Socio-Technical Scenarios -- Information and Imagination: How Lux Research Forecasts -- Designing for the Future: Nanoscale Research Facilities -- What Drives Public Acceptance of Nanotechnology? -- Nanologue -- Anticipating the Futures of Nanotechnology: Visionary Images as Means of Communication -- Winners of Nano-Hazard Symbol Contest Announced atWorld Social Forum, Nairobi, Kenya -- Your Children, Their Children$1! = (B-- Developing Plausible Nano-Enabled Products -- Nanotechnology for Chemical and Biological Defense 2030 Workshop and Study -- Nanotechnologies for Tomorrow$1 (Bs Society: A Case for Reflective Action Research in Flanders, Belgium -- Communications in the Age of Nanotechnology -- How Can Business Respond to the Technical, Social, and Commercial Uncertainties of Nanotechnology? -- Manufactured Nanoparticle Health and Safety Disclosure [Draft Report] -- A Framework for Responsible Nanotechnology -- Contemplating the Implications of a Nanotechnology (3z(BRevolution(3y (B-- Nanotechnology: Challenges and the Way Forward -- Technology Assessment of Nanotechnology: Problems and Methods in Assessing Emerging Technologies -- Compressed Foresight and Narrative Bias: Pitfalls in Assessing High Technology Futures -- Science Fiction, Nano-Ethics, and the Moral Imagination.s
Keywords: Business; Management; Industrial management; Popular works; Environmental law; Environmental policy; Economic policy; Social sciences; Nanotechnology; Business and Management; Innovation/Technology Management; Nanotechnology; Social Sciences, general; Environmental Law/Policy/Ecojustice.; R & D/Technology Policy; Popular Science, general; Electronic books